Understanding the coupled relationship between regional longevity and physical geographical environment in Hechi, Guangxi, China - Qucheng Deng; Yaqing Liu; Yongping Wei; Wei Liang; Kaixian Zhu; Yonghua Li; Lihai Zhang (Scientific Reports)
Abstract Healthy ageing plays an important role in ageing societies in many countries, and centenarians are a sign of longevity. Longevity and its determinants have become issues of global concern and also a focus of research. Although many disciplines have conducted out a series of studies on longevity phenomena, few studies have systematically considered the impact of geographical environmental factors. Guangxi is one of the provinces with the highest centenarian ratio in mainland China, while Hechi City has the highest ratio of centenarians in Guangxi Province, and contains the world-famous longevity belt. This study took Hechi City, “the world’s longevity city”, as a model research area. First, the basic characteristics of the geographical environmental factors in Hechi City were analysed, and then geographical information system techniques and eXtreme Gradient Boosting machine learning methods were applied to systematically analyse the coupling relationship between the spatial distribution of the longevity population and the geographical environmental factors. In addition, the geographical environmental factors closely related to longevity were filtered and investigated. It was found that the centenarian is distributed along a belt-like pattern. It is mostly located in rocky mountainous areas with low elevations, small to medium undulations, medium slopes and brown calcareous soils, but is rarely found near the non-ferrous mining industry. This work provides a scientific basis for identifying the mechanisms that contribute to regional longevity and theoretical references for improving the health level of the elderly population according to local conditions.